2016
DOI: 10.1371/journal.pone.0158780
|View full text |Cite
|
Sign up to set email alerts
|

Health Worker Compliance with a ‘Test And Treat’ Malaria Case Management Protocol in Papua New Guinea

Abstract: The Papua New Guinea (PNG) Department of Health introduced a ‘test and treat’ malaria case management protocol in 2011. This study assesses health worker compliance with the test and treat protocol on a wide range of measures, examines self-reported barriers to health worker compliance as well as health worker attitudes towards the test and treat protocol. Data were collected by cross-sectional survey conducted in randomly selected primary health care facilities in 2012 and repeated in 2014. The combined surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…Although this may show some improvements in blood testing, more work still needs to be done in ensuring adherence to testing requirements. In treating malaria, compliance with the recommended first-line medication for uncomplicated malaria was also found to be low in many country-level studies 30 31. A cross-country study showed that less than a third of fevers were treated according to the national guidelines and only about 40% on fevers on average (ranging from 8% to 72%) were managed effectively 32.…”
Section: Discussionmentioning
confidence: 99%
“…Although this may show some improvements in blood testing, more work still needs to be done in ensuring adherence to testing requirements. In treating malaria, compliance with the recommended first-line medication for uncomplicated malaria was also found to be low in many country-level studies 30 31. A cross-country study showed that less than a third of fevers were treated according to the national guidelines and only about 40% on fevers on average (ranging from 8% to 72%) were managed effectively 32.…”
Section: Discussionmentioning
confidence: 99%
“…ACPR in AL-treated patients was comparable to two other studies carried out in children aged 0.5–5 years in Madang and East Sepik provinces (Karunajeewa et al day 42 ACPR 95.2% [ 6 ]; Laman et al day 42 ACPR 97.8% [ 11 ]. The two recrudescent infections observed in the AL arm on day 42 underline the importance of continued monitoring of the efficacy of AL in the context of increasing use of the regimen in public facilities and persisting availability of monotherapy [ 21 ]. ACPR to DHA-PPQ was higher in this study (day 42: 97.8%, 95% CI 93.2–99.4) than in the previous trial conducted by Karunajeewa et al in 2005–2007 (day 42: 88%, 95% CI 80–93.6) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“… 32 Nevertheless, although the treatment’s gametocidal effect can reduce transmission from patients, its prophylactic effect is limited. Moreover, in 2014, only 45% of patients with confirmed or suspected malaria who attended health-care facilities were treated with artemisinin-based combination therapy, 33 which corresponds to a population coverage of 19% at best. The community benefits of combination therapy can be maximized by prompt diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%